2020
DOI: 10.1101/2020.03.10.986646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial function and genital inflammation in young South African women at high risk of HIV infection

Abstract: Female genital tract (FGT) inflammation is an important risk factor for HIV acquisition. Previous studies have identified the FGT microbiota as a major determinant of altered inflammatory cytokine profiles, however, the relative importance of microbial activities and functions is unknown. Liquid chromatography-tandem mass spectrometry was used to evaluate the FGT metaproteomic profiles of 113 young South African women. FGT inflammation was defined by inflammatory cytokine concentration profile. A total of 3,18… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Samples were computational randomised and the eluted material subjected to metaproteomic analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS) on a Q-Exactive quadrupole-Orbitrap MS (Thermo Fisher Scienti c, MA, USA) coupled with a Dionex UltiMate 3000 nano-UPLC system (120min per sample) [45]. Proteomic data were used to infer vaginal microbiome composition and host secretome as described previously [45].…”
Section: Metaproteomics Analysis Of Cervicovaginal Swab Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were computational randomised and the eluted material subjected to metaproteomic analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS) on a Q-Exactive quadrupole-Orbitrap MS (Thermo Fisher Scienti c, MA, USA) coupled with a Dionex UltiMate 3000 nano-UPLC system (120min per sample) [45]. Proteomic data were used to infer vaginal microbiome composition and host secretome as described previously [45].…”
Section: Metaproteomics Analysis Of Cervicovaginal Swab Samplesmentioning
confidence: 99%
“…Samples were computational randomised and the eluted material subjected to metaproteomic analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS) on a Q-Exactive quadrupole-Orbitrap MS (Thermo Fisher Scienti c, MA, USA) coupled with a Dionex UltiMate 3000 nano-UPLC system (120min per sample) [45]. Proteomic data were used to infer vaginal microbiome composition and host secretome as described previously [45]. Brie y, proteins were identi ed using two different databases: (i) UniProt database restricted to human and microbial entries (73,910,451, release August-2017) and ltered using the MetaNovo pipeline [48]; (ii) human proteins combined with a vaginal metagenome-based database obtained from the study of A uni-Zadeh et al [49].…”
Section: Metaproteomics Analysis Of Cervicovaginal Swab Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins will be identified using a custom UniProt database including human and vaginal microbial entries. Taxonomy will be assigned using UniProt and relative abundance of each taxon will be determined by aggregating the intensity-based absolute quantification (iBAQ) values of all proteins identified for each taxon [41].…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…We have a poor understanding of, and ability to accurately measure, metabolic products relevant to the optimal and dysbiotic VMB including short chain fatty acids and lactic acid (Aldunate et al, 2015 ). Metaproteomic analysis of mucosal inflammation and target cell activation in a cohort of African women has shown that minority microorganisms may have disproportionate metabolic activity and functional impact (Alisoltani et al, 2020 ). However, at this stage reference database limitations undermine the reliability of metaproteomics approaches.…”
Section: Profiling the Vaginal Microbiotamentioning
confidence: 99%